Occurrence of coliphage in effluent: A systematic literature review and meta-analysis - Kaedra R. Jones; Sorina Eftim; Alexander J. Lindahl; Steven Black; Sharon P. Nappier (Elsevier, 2022)
Studies have illustrated that wastewater treatment methods targeting bacteria do not remove all types of viruses and available epidemiological studies indicate bacteria concentrations may not always be predictive of viral illnesses associated with recreational water exposure. To address these challenges, coliphages have been proposed as an indicator of fecal contamination in recreational water. When compared to traditional fecal indicator bacteria, coliphages exhibit a longer persistence in the environment. The persistence of coliphages in the environment and through wastewater treatment more closely resembles that of pathogenic viruses. We conducted a systematic literature search of peer-reviewed publications to identify coliphage density data (somatic [SC] and male-specific [MSC]) in wastewater treatment plant (WWTP) effluent categorized as primary, secondary, tertiary treated, or disinfected. Scope, study quality, and data availability were included as literature review inclusion criteria. An analysis was conducted to estimate the coliphage densities for specific treatment types within each respective WWTP effluent category. Densities of MSC and SC in influent were significantly higher when compared to densities of MSC and SC in effluent subjected to secondary treatment using biological treatment processes both with and without nutrient removal, tertiary treatment using either a treatment pond or a phosphate removal process, or disinfection using either chlorine, UV, or a combination of both UV and chlorine. Distributions of coliphage in various wastewater effluents will be useful for evaluating the efficacy of treatment processes and disinfectants in future microbial risk assessments.